SPECIFIC FEATURES OF TEACHING POLYSEMY IN SENIOR STUDENTS (Academicia Globe: Inderscience Research, 2022)
The development of speech is an urgent task of teaching in elementary school. Speech is a way of knowing reality, it performs the functions of communication, emotional self-expression of a person and influence on other people. Speech development contributes to the development of the pupil’s thinking. In this article author describes some possible methods of teaching polysemy to senior pupils.